COVID-19-Associated Hyper-Fibrinolysis: Mechanism and Implementations - Jacob, Giris; Aharon, Anat; Brenner, Benjamin (Frontiers in Physiology, 2020)
The emerging novel coronavirus disease (COVID-19), which is caused by the SARS-CoV-2 presents with high infectivity, morbidity and mortality. It presenting a need for immediate understanding of its pathogenicity. Inflammation and coagulation systems are over-activated in COVID-19. SARS-CoV-2 damages endothelial cell and pneumocyte, resulting in hemostatic disorder and ARDS. An influential biomarkers of poor outcome in COVID-19 are high circulating cytokines and D-dimer level. This latter is due to hyper-fibrinolysis and hyper-coagulation. Plasmin is a key player in fibrinolysis and is involved in the cleavage of many viruses envelop proteins, including SARS-CoV. This function is similar to that of TMPRSS2, which underpins the entry of viruses into the host cell. In addition, plasmin is involved in the pathophysiology of ARDS in SARS and promotes secretion of cytokine, such as IL-6 and TNF-α, from activated macrophages. Here, we suggest an out-of-the-box treatment for alleviating fibrinolysis and the ARDS of COVID-19 patients. This proposed treatment is concomitant administration of an anti-fibrinolytic drug and the anticoagulant.